Android-Based Community Security and Order Monitoring Application using Haversine Formula - Yudhi Setyo Purwanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Security and public order issues are not the responsibility of the government and the police department only, but also the community. The low level of awareness of the urban/sub-urban community in the community security and order (CSO) program is caused by the community's fast-paced lifestyle, focusing on work, and often leaving their houses for a long-term period. An alternative solution that can be offered is to create an application related to the program in the village level. This application, besides being able to support CSO and involve all residents, can also increase mutual trust, communication, and social relations between them. The result is a Smart Warning Application that combines integrated security and order control functions. This application was created to help residents within the village and includes ten functions that are commonly used to provide information to each other in the surrounding area. Government officials can monitor and access the application through the website provided. The existing information will be inventoried and stored so that at the end, it can be used as a reference for making plans to improve public security and order in the future. Keywords: community security and order, village, state apparatus, geo-tagging, haversine